Human rights protection by the ECtHR and the ECJ : a comparative analysis in light of the equivalency doctrine - Ravasi, Elisa (International studies in human rights, 2017)
In her manuscript Elisa Ravasi examines how the ECtHR responds to the growing challenges of overlapping legal systems. She focuses, in particular, on the relationship between the ECHR and EU law. First, she systematically analyses 10 years of ECtHR jurisprudence on the principle of equivalent protection and develops an innovative analysis scheme for its application. Afterwards, she examines the equivalency of the human rights protection provided by the ECJ in light of the minimum standards of the ECHR in three specific fields (naming law, ne bis in idem and equality of arms). Finally, she considers whether the presumption of equivalent protection of the ECtHR in favour of the EU is still justified.